EDUCATION REGARDING EARLY DETECTION AND EARLY TREATMENT OF BRAIN TUMORS IN BANYUWANGI REGENCY, INDONESIA - Susilo, Rahadian Indarto; Haq , Irwan Barlian Immadoel; Apriawan, Tedy; Wahyuhadi, Joni; Puspikawati, Septa Indra; Ramadhaningtyas , Erica Medina (Journal of Public Health Research and Community Health Development, 2025)
Brain tumors were estimated to occur at 6.4 per 100,000 people each year. The incidence rate of brain tumors in children is reported to be 5.7% out of every 100,000 children, while in adults, the reported rate is significantly higher at 29.9% out of every 100,000 people. Banyuwangi Regency has an area of 5,782.50 km2 with a population in 2018 of 1,609,677 people with a density of around 278 people/km2. With such a large population, early detection of brain tumors is important for the public to understand. Early detection activity programs from community health centre need to be held with the hope that health workers will be able to provide education and information regarding early symptoms and signs of brain tumors as well as risk factors for brain tumors for prevention. Increasing public knowledge about alerting the early symptoms of brain tumors is one strategy that can be used to reduce death and disability rates due to brain tumors. The aim of this community service program is to increase the knowledge of the lay public and health workers regarding early detection and early treatment of brain tumors in Banyuwangi Regency. Pre- and post-test questionnaires were given before and after the material to evaluate the increase in knowledge about brain tumors for lay people and health workers in Banyuwangi Regency. The results obtained a significant increase (p < 0.01) between the pre-test and post-test scores so that this community service increases the knowledge of the community in Banyuwangi Regency.